Physiology secrets : [questions and answers reveal the secrets to understanding physiology] - Raff, Hershel (Hanley & Belfus, 2003)
Medical College of Wisconsin, Milwaukee. Reviews physiology from the cellular level, by organ system, and as integrative systems. Includes a final examination with answer key for each chapter. Features tips, question-and-answer format, and a detailed index. Previous edition: c1999. Softcover.
Keywords: Physiology; fyziologie